HUBUNGAN ANTARA PENDIDIKAN DAN SOSIAL EKONOMI KELUARGA DENGAN STATUS GIZI BALITA DI PUSKESMAS KERAMASAN PALEMBANG TAHUN 2012 - Dini Kesumah Dini Kesumah (STIKes Budi Mulia Sriwijaya, 2012)
ABSTRACT According to World Health Organization Health Organization (WHO) in 2005 showed 49% of deaths occur in children under five in developing countries. Nutritional problems can not be done with the medical and health care approach alone. Causes related to malnutrition that maternal education, socioeconomic families, poor environmental sanitation, and lack of food supplies. This study aims to determine the relationship between education and socioeconomic status of families with nutrition survey using a cross sectional analytic approach, with a population of all mothers of children under five who visited the health center in Palembang Keramasan Accidental sampling Sampling the number of samples obtained 35 respondents. Variables include the study independent and dependent variables and univariate analysis using Chi-Square test statistic with a significance level α = 0.05. The results from 35 respondents indicate that highly educated mothers earned as many as 16 people (45.7%), and middle and upper income families as many as 12 people (34.3%) and bivariate test results show that highly educated respondents toddler nutritional status good for 81.3% (13 people) is larger than the less educated respondents balitanya good nutritional status 26.3% (5 persons) as well as respondents who have middle and upper socioeconomic families with good nutritional status of children at 91.7% ( 11 people) is larger when compared to respondents who have family socioeconomic medium with good nutritional status of children at 30.4% (7 people). Statistical tests show that education has a significant relationship with nutritional status of children P value = 0.004 and socioeconomic families have a meaningful relationship with nutritional status of children P value = 0.002. Based on the results of the study suggested the health professionals in the health center should further improve the education, information about the importance of nutrition to the development of the child in the mothers through the selection and processing of good food and a good diet through health centers and integrated health. ABSTRAK Menurut badan kesehatan World Health Organization (WHO) tahun 2005 menunjukkan 49% kematian yang terjadi pada anak dibawah umur lima tahun di negara berkembang. Masalah gizi ini tidak dapat dilakukan dengan pendekatan medis dan pelayanan kesehatan saja. Penyebab yang berhubungan dengan kurang gizi yaitu pendidikan ibu, sosial ekonomi keluarga, sanitasi lingkungan yang kurang baik,dan kurangnya persediaan pangan. Penelitian ini bertujuan untuk mengetahui hubungan antara pendidikan dan sosial ekonomi keluarga dengan status gizi balita dengan menggunakan metode survei analitik pendekatan secara Cross Sectional, dengan populasi semua ibu yang memiliki anak balita yang berkunjung ke Puskesmas Keramasan Palembang dengan pengambilan sampel secara Accidental Sampling diperoleh jumlah sampel 35 responden. Variabel penelitian meliputi variabel independen dan dependen serta analisis univariat menggunakan uji statistik Chi-Square dengan tingkat kemaknaan α = 0,05. Hasil penelitian ini menunjukkan dari 35 responden didapatkan ibu yang berpendidikan tinggi sebanyak 16 orang (45,7%), dan keluarga yang berpenghasilan menengah keatas sebanyak 12 orang (34,3%) dan hasil uji bivariat menunjukkan bahwa responden yang berpendidikan tinggi status gizi balitanya baik sebesar 81,3% (13 orang) lebih besar bila dibanding responden yang berpendidikan rendah status gizi balitanya baik 26,3% (5 orang) serta responden yang mempunyai sosial ekonomi keluarga menengah keatas dengan status gizi balita baik sebesar 91,7% (11 orang) lebih besar bila dibanding responden yang mempunyai sosial ekonomi keluarga menengah kebawah dengan status gizi balita baik sebesar 30,4% (7 orang). Uji statistik menunjukkan bahwa pendidikan mempunyai hubungan yang bermakna dengan status gizi balita P value = 0,004 dan sosial ekonomi keluarga mempunyai hubungan yang bermakna dengan status gizi balita P value = 0,002. Berdasarkan hasil penelitian disarankan pada petugas kesehatan di Puskesmas hendaknya lebih meningkatkan penyuluhan-penyuluhan tentang pentingnya gizi terhadap tumbuh kembang anak pada ibu-ibu melalui cara pemilihan dan pengolahan bahan makanan yang baik serta pola makanan yang baik melalui kegiatan Puskesmas dan Posyandu.